Gender dysphoria assessment and action for youth: Review of health care services and experiences of trans youth in Manitoba. Issue 3 (23rd November 2017) - Heard, Jack; Morris, Amanda; Kirouac, Nicole; Ducharme, Jennifer; Trepel, Simon; Wicklow, Brandy
Abstract: Objectives: To describe the paediatric transgender population accessing health care through the Manitoba Gender Dysphoria Assessment and Action for Youth (GDAAY) program, and report youth's experiences accessing health care in Manitoba. Methods: Demographic, medical, surgical and mental health information was extracted from the medical records of youth referred to the GDAAY program (n=174). A 77-item online survey was conducted with a subset of those youth (n=25) to identify common health care experiences and perceptions of trans youth in Manitoba. Results: Chart review of 122 natal females and 52 natal males, ranging in age from 4.7 to 17.8 years (mean 13.9 years), found 66 patients (46.8%) with a pre-existing or current mental health diagnosis, of which anxiety and depression were the most common (n=43, 30.5%). Qualitative self-reports revealed all patients had negative interactions with health care providers at some point, many having experienced lack of engagement with the medical system due to reported lack of knowledge by the provider on trans-related health services. Conclusion: Transgender youth in Manitoba seeking GDAAY services have high rates of anxiety and depression. These youth face adversity in health care settings and are distressed over long wait times for mental health services. Recommendations to improve care include increasing general health care providers' education on gender affirmative care, providing gender sensitivity training for health care providers, gathering preferred names and pronouns during triage, increasing visibility of support for LGBT+ persons in clinics, increasing resource allocation to this field and creating policies so all health care settings are safe places for trans youth.